The Influence of The Female Daily Community (FD Talk) as a Reference Group on Intention to Purchase Beauty Products - Della Aniswara; Ajeng Dhyanti Paramitha (Green Publisher Indonesia, 2024)
The purpose of this study is to determine how much of an impact The Female Daily Community (FD Talk), a reference group, has on customers' intentions to buy cosmetic items. Online communities are crucial in influencing customer behavior in today's digital environment, especially in the competitive and ever-changing beauty market. This study investigates how much FD Talk influences consumers' attitudes, preferences, and buy intentions in the beauty sector through qualitative interviews. The results highlight the significant influence of FD Talk as an online community, offering insightful information to marketers looking to use online communities for tactical marketing campaigns. Comprehending the interplay between virtual reference groups and customer behavior is crucial for enterprises seeking to effectively interact with their intended market.